The Importance Of Pedagogical Approaches To Primary Education Administration - Eshmanova N. N.; Matupayeva Sh. Z. (Euro Asian Journal Publishing, 2024)
This article presents the most important pedagogical sources related to the management of primary education from the oldest, middle and new eras. In this, their knowledge and experiences are highlighted.
Keywords: experience; Beginning; education; foundation